Inhibitory effects of thymol on the cytotoxicity and inflammatory responses induced by Staphylococcus aureus extracellular vesicles in cultured keratinocytes. (September 2019) - Kwon, Hyo Il; Jeong, Na Hee; Kim, Se Yeon; Kim, Mi Hyun; Son, Joo Hee; Jun, So Hyun; Kim, Shukho; Jeon, Hyejin; Kang, Sun Chul; Kim, Sang Hyun; Lee, Je Chul
Abstract: Staphylococcus aureus extracellular vesicles (EVs) deliver effector molecules to host cells and induce host cell pathology. This study investigated the disruption of S. aureus EVs by thymol along with its inhibitory effects on the cytotoxicity and inflammatory responses induced by EVs derived from two different S. aureus strains in cultured keratinocytes. Membrane disruption of the S. aureus EVs treated with thymol was determined using transmission electron microscopy. Human keratinocyte HaCaT cells were incubated with either intact or thymol-treated S. aureus EVs and then analyzed for cytotoxicity and pro-inflammatory cytokine gene expression. Thymol inhibited the growth of S. aureus strains and disrupted the membranes of the S. aureus EVs. The cytotoxicity and the expression levels of the pro-inflammatory cytokine genes towards HaCaT cells differed between the EVs derived from two S. aureus strains. Thymol-treated S. aureus EVs inhibited the cytotoxicity and the expression of the pro-inflammatory cytokine genes when compared to intact S. aureus EVs. Thymol-treated S. aureus EVs delivered lesser amounts of the EV component to host cells than intact EVs. Our results suggest that the thymol-induced disruption of the S. aureus EVs inhibits the delivery of effector molecules to host cells, resulting in the suppression of cytotoxicity and inflammatory responses in keratinocytes. Thymol may attenuate the host cell pathology induced by an S. aureus infection via both the antimicrobial activity against the bacteria and the disruption of the secreted EVs. Highlights: EVs derived from S. aureus induce host cell pathology. Thymol disrupts the membrane of the S. aureus EVs. Thymol-treated S. aureus EVs suppress the host cell pathology. EVs from different S. aureus strains exhibit different susceptibilities to thymol.